Effects of obesity on circadian photic entrainment of locomotor activity in wild mice Neotomodon alstoni. Issue 4 (3rd July 2016) - Miranda-Anaya, Manuel; Carmona-Alcocer, Vania; Carmona-Castro, Agustín
Abstract: Obesity is increasing in industrialized countries at an alarming rate. Recent studies have linked this condition with changes in the circadian regulation, and circadian clock dysfunctions have also been linked to metabolic disorders. When in captivity and fed a regular rodent chow diet ad libitum some volcano mice, Neotomodon alstoni (endemic species of Mexico) become overweight and display symptoms equivalent to metabolic syndrome. The aim of this work was to observe whether there are significant changes in the functional properties of the circadian system, namely in the entraining circadian locomotor activity rhythm, between mice that became obese and normal adult mice. Freely moving circadian rhythms of locomotor activity were tested under constant conditions as well as under conditions of discrete and continuous entrainment. Our results show that volcano lean mice present a phase response curve with larger delays than advances, indicating that re-entrainment is more easily achieved by delays. Volcano obese mice are less efficient at re-entraining because they show smaller phase shifts in delays than control mice. These results indicate that obesity in N. alstoni has a negative effect on the circadian mechanisms that integrate the photic entrainment.